SHOCK INDEX AS A PREDICTOR OF HYPERLACTATEMIA FOR EARLY DETECTION OF SEVERE SEPSIS IN PATIENTS PRESENTING TO EMERGENCY DEPARTMENT OF A LOW TO MIDDLE INCOME COUNTRY - Waheed, Shahid; Ali, Noman; Sattar, Sidra; Siddiqui, Emaduddin (Journal of Ayub Medical College Abbottabad, 2020)
Introduction: The epidemiology of Systemic Inflammatory Response Syndrome (SIRS) has been poorly understood accounts 17.8% annually 16.6 million adult per year. An agreement between Shock Index and Serum Lactate levels to reported to be 83%. With limited health resources in a low to middle income country, the need of markers that are non-invasive, cost effective. Shock index can serve this purpose as a surrogate marker of disease severity in patients with severe sepsis and thus resulting in early detection. Methods: This cross-sectional study was conducted from December 2014 to May 2015 at a tertiary care setup (Aga Khan University Hospital) in Karachi consisting of all septic patient received at the emergency department. Non-probability sampling technique was used. P-value <0.05 was taken as significant. Results: Out of 180 study participants 94 (52.22%) were males while 86 (47.78%) were females. The mean age was 57.48 ± 18.8 years. Shock index with cut off value of > 0.7 was used and moderate to strong agreement between the two was found with kappa Îº = 0.786 (p = .000). Sensitivity was found to be 0.99, specificity 0.75, NPV 0.98, PPV 0.87. Conclusion: Shock index has very favorable features, availability, direct relevance to sepsis. A high SI predicts elevated lactate levels in patients with sepsis. Background: Early detection of sepsis in emergency department is of prime importance and require tools that are time and cost- effective. The Systemic Inflammatory Response Syndrome (SIRS) has been poorly associated with sepsis. Timothy et al in a retrospective analysis of Emergency Department (ED) visits stated estimate of SIRS at 17.8% accounting to an annual yield of 16.6 million adult visits with SIRS per year, among these only 26% accounted as an infectious aetiology of SIRS, trauma being 10% and other causes being rare. Shock index is found to be independently associated with 30-day mortality in a broad population of ED patients including sepsis. With limited health resources in a low to middle income country, focused utilization is important and so is the need of markers that are non-invasive, readily available, cost effective and easy to interpret. Shock index can serve this purpose as a surrogate marker of disease severity in patients with severe sepsis and thus resulting in early detection of such patients. Methods: This cross-sectional study was conducted from December 2014 to May 2015 at a tertiary care setup (Aga Khan University Hospital) in Karachi consisting of all septic patient received at the emergency department. Non-probability sampling technique was used. p-value <0.05 was taken as significant. Results: Out of 180 study participants 94 (52.22%) were males while 86 (47.78%) were females. The mean age was 57.48±18.8 years. Cohen's Îº was used to determine an agreement between Shock index and Lactate levels. Shock index with cut off value of > 0.7 was used and moderate to strong agreement between the two was found with kappa Îº = 0.786 which was statistically significant (p=<0.001). Sensitivity was found to be 0.99, specificity 0.75, NPV 0.98, PPV 0.87. Conclusion: To conclude shock index has some very favourable features, including availability, low cost and direct relevance to sepsis in terms of its high validity. A high SI predicts elevated lactate levels in patients with sepsis. Keywords: Sepsis; severe sepsis; septic shock; lactate levels; shock index